Understanding Tick Biology and Its Implications in Anti-tick and Transmission Blocking Vaccines Against Tick-Borne Pathogens - Bhowmick, Biswajit; Han, Qian (Frontiers in Veterinary Science, 2020)
ABSTRACT Ticks are obligate blood-feeding ectoparasites that transmit a wide variety of pathogens to animals and humans in many parts of the world. Currently, tick control methods primarily rely on the application of chemical acaricides, which results in the development of resistance among tick populations and environmental contamination. Therefore, an alternative tick control method, such as vaccines have been shown to be a feasible strategy that offers a sustainable, safe, effective and environment-friendly solution. Nevertheless, novel control methods are hindered by a lack of understanding of tick biology, tick-pathogen-host interface and identification of effective antigens in the development of vaccines. This review highlights the current knowledge and data on some of the tick-protective antigens that have been identified for the formulation of anti-tick vaccines along with the effects of these vaccines on the control of tick-borne diseases. Keywords: Anti-tick vaccine, Ixodes, Borrelia, Transmission-blocking vaccine, Blood digestion, Saliva-assisted transmission